Analysis of the Function of Code Mixing in the Lyrics of Javanese Pop Songs by Denny Caknan - Fathurohman, Irfai; Syaifuddin, Ahmad; Ristiyani; Roysa, Mila; Hidayati, Nur Alfin (ICCCM Journal of Social Sciences and Humanities, 2023)
This research aims to describe the function of code mixing in the lyrics of Javanese pop songs by Denny Caknan. The researcher focuses on the function of code mixing in Seowito theory (Nabila & Kustriyono, 2022). Data analysis techniques in research use the theory put forward by Miles and Huberman (Latifah & Supena, 2021). Code mixing is the science of studying language speech caused by communication with other individuals or groups. Social media is a digital platform that has a very wide network, with the development of the times human interaction can be done easily and sophisticatedly through social media. Code mixing in the lyrics of Javanese pop songs by Denny Caknan, several functions of code mixing that occurred in this research were found. in inserting code mixing in the form of words, phrases, clauses and repetition. The code-mixing function found in the research on the lyrics of the Javanese pop song by Denny Caknan, there was a total of 28 data found in this research with the details, namely: code mixing function used to emphasize a certain meaning 12 data, to show self-identity 2 data and influence regarding the issues discussed 14 data.